Avaliação de ciclo de vida ambiental e econômica da pecuária leiteira em sistema Compost Barn - Franciane Gabrielle dos Santos (2024)
Dairy farming has great socioeconomic importance in Brazil, and in recent decades has recorded a constant evolution of the production chain, seeking to increase the quality of the product and the efficiency of this activity. In this context, production systems have intensified and adopted new technologies. In addition to the quest for greater productive efficiency, the environmental sustainability of agricultural systems has been increasingly discussed, and dairy farming is associated with a series of potential environmental impacts, making it essential to identify and mitigate them for the consolidation of a sustainable production chain. The compost barn system has stood out as a confinement option for dairy cattle, due to its lower implementation cost compared to other stabled systems and the possibility of providing an appropriate destination for animal waste. Therefore, the objective of this work was to evaluate the environmental life cycle and economic feasibility of implementing a compost barn system on a dairy farm located in the municipality of Bocaiúva, in the semi-arid northern region of Minas Gerais. In the Life Cycle Assessment (LCA), the impact categories of climate change, terrestrial acidification, and freshwater eutrophication were evaluated. Economic feasibility was assessed through the compilation and analysis of gross revenue, net revenue, costs and expenses, cash flow, depreciation and amortization, opportunity cost, minimum attractiveness rate (MAR), net present value (NPV), internal rate of return (IRR), discounted payback, profitability index, and breakeven point. The production of 1 kg of fat- and protein-corrected milk on the evaluated property is associated with a carbon footprint of 1.6698 kg CO2-eq, terrestrial acidification of 0.003443 kg SO2-eq, and freshwater eutrophication of 0.000289 kg PO4-eq. Investment in the compost barn system proved to be economically viable, with an NPV of R$541,487.17, an IRR of 44.83%, and a payback of 2.56 years. The adoption of the compost barn system on the property contributed both to a carbon footprint below the global average and to the economic viability of the activity.